Empowering Fish Cultivator Groups in Water-Minimum Areas by Cultivating Ospronemous gouramy Fish in Probiotic Media Tarpaulin Ponds in Asahduren Village, Jembrana Regency, Bali Province - I Wayan Arya; I Gusti Gurah Sugiana; I Dewa Nyoman Sadguna; I Gede Sudiarta; N. Pangki Pangemanan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This National Community Partnership Program (PKM) is a collaboration between Warmadewa University, Denpasar and Sam Ratulangi University, Manado with partner fish cultivator group (Pokdakan)